2013
DOI: 10.1108/edi-01-2010-0007
|View full text |Cite
|
Sign up to set email alerts
|

Fostering trust in mentoring relationships: an exploratory study

Abstract: Purpose -Mentoring has been identified as a key strategy to career development and has been argued to be indispensable for women to advance to positions of power. For mentoring to succeed, it is imperative that mentors trust their protégés. However, recent research has suggested that male mentors trust their male protégés more so than their female protégés. Since women are frequently mentored by men, it is imperative that they gain the same level of trust as their male peers enjoy. According to an established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 53 publications
3
31
0
Order By: Relevance
“…In a mentoring relationship trust is built over time (Leck & Orser, 2013). The development of a trusting rapport was pivotal in the decision to undertake the thesis by publication.…”
Section: The Decision To Undertake the Thesis By Publicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a mentoring relationship trust is built over time (Leck & Orser, 2013). The development of a trusting rapport was pivotal in the decision to undertake the thesis by publication.…”
Section: The Decision To Undertake the Thesis By Publicationmentioning
confidence: 99%
“…These are all important in varying degrees and independent of each other (Mayer et al, 1995). Initially a mentor may trust a protégé because of a perception of these qualities (Leck & Orser, 2013) but over time a more equitable working process should be built in which protégés feel they could take initiative and participate in decision making. Trust by both partners is essential and is initially bestowed then confirmed and extended.…”
Section: Introductionmentioning
confidence: 99%
“…When entering the mentoring relationship, millennial women should not expect the process to be obstacle‐free. Leck and Orser () posited that developing trust can be more difficult if the mentor is male and the mentee is female. They stated that the “…female mentors felt that female protégé's with female mentors held more trusting relationships.…”
Section: Leadership Behavior and Styles Mattermentioning
confidence: 99%
“…Trust is essential in a mentoring relationship as the mentee must take risks within the relationship to achieve the mentoring goals and previous research has suggested that mentoring is effective only when trust is formed between mentors and mentees [23]. However, what establishes mutual trust, respect and commitment with individuals who have never met face-to-face?…”
Section: Limitations Of E-mentoringmentioning
confidence: 99%